SEJARAH PELABUHAN BARUS 1901-1983 - As Meuraxa, Rahmad Fauzan; Suri, Nursukma (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
The research entitled "History of Barus Harbor (1901-1983)" aims to find out the background of the establishment of Baru Harbor, the goods traded, who carried out the trade from the Dutch Colonial period to the New Order era, the causes of Barus Harbor experiencing decline and the impact The decline of Barus Harbor lasted from 1901-1983. The method used in this research is a historical method which has four stages, namely: heuristics, source criticism, interpretation, and explanation using a maritime history approach. Based on the research results, it is known that the background to the establishment of the Barus port was because the trading port at Kadei Gadang was not safe for merchant ships to dock, so the colonial government built the Barus Port, while the goods traded by the local population were camphor, resin, salt, incense. exchanged for Chinese merchandise such as ceramics, the Mandailing people traded Malay songket, while the Dutch traded watches and ceramics. The decline in trade at Barus Harbor was caused by sea abrasion, as a result Barus harbor was no longer the main port, because a safer harbor was built in Pasar Tarandam.